The first case report of a solitary metastasis of the transitional cell carcinoma of the ovary to the spleen - Lazović, Ranko; Vukčević, Batrić; Milić, Petar; Lazović, Jelena (Vojnosanitetski pregled, 2022)
Background. Primary transitional cell carcinoma (TCC) of the ovary is characterized by the presence of papillary projections of malignant transitional epithelial cells or their aggregates in the fibrous stroma. This type of tumor represents nearly 1% of all ovarian surface epithelium carcinomas. We presented the first report of a solitary splenic metastasis of primary ovarian TCC. Case report. A 60-year-old female patient was admitted because of an asymptomatic splenic tumor in December 2018. Two years prior, she underwent a total abdominal hysterectomy, bilateral adnexectomy, and infracolic omentectomy for the primary TCC of the ovary. Control abdominal ultrasonography, computed tomography, and magnetic resonance imaging performed two years after primary surgery showed a splenic tumor. An open splenectomy was performed, with the intraoperative finding of a hilar splenic tumor and the absence of other pathological lesions in the abdomen. Frozen section analysis showed a TCC metastasis, which was subsequently confirmed by definitive histopathological examination. During the one-year follow-up, there was no relapse of the disease. Conclusion. This is the first report of a solitary splenic metastasis of primary ovarian TCC based on the literature review. This case may serve as an example of the diagnostic and therapeutical role of splenectomy in isolated splenic metastases of ovarian cancer.
Keywords: carcinoma, transitional cell; diagnosis; histological techniques; neoplasm metastasis; ovarian neoplasms; spleen